A Qualitative Study of Self and Caregiver Perspectives on How Autistic Individuals Cope With Trauma - Ng-Cordell, Elise; Rai, Anika; Peracha, Hira; Garfield, Tamara; Lankenau, Stephen E.; Robins, Diana L.; Berkowitz, Steven J.; Newschaffer, Craig; Kerns, Connor M. (Frontiers in Psychiatry, 2022)
Background: Coping can moderate the relationship between trauma exposure and trauma symptoms. There are many conceptualisations of coping in the general population, but limited research has considered how autistic individuals cope, despite their above-average rates of traumatic exposure. Objectives: To describe the range of coping strategies autistic individuals use following traumatic events. Methods: Fourteen autistic adults and 15 caregivers, recruited via stratified purposive sampling, completed semi-structured interviews. Participants were asked to describe how they/their child attempted to cope with events they perceived as traumatic. Using an existing theoretical framework and reflexive thematic analysis, coping strategies were identified, described, and organised into themes. Results: Coping strategies used by autistic individuals could be organised into 3 main themes: (1) Engaging with Trauma, (2) Disengaging from Trauma, and (3) Self-Regulatory Coping. After the three main themes were developed, a fourth integrative theme, Diagnostic Overshadowing, was created to capture participants’ reports of the overlap or confusion between coping and autism-related behaviours. Conclusions: Autistic individuals use many strategies to cope with trauma, many of which are traditionally recognised as coping, but some of which may be less easily recognised given their overlap with autism-related behaviours. Findings highlight considerations for conceptualizing coping in autism, including factors influencing how individuals cope with trauma, and how aspects of autism may shape or overlap with coping behaviour. Research building on these findings may inform a more nuanced understanding of how autistic people respond to adversity, and how to support coping strategies that promote recovery from trauma.